Comparison of laboratory-scale methods for assessing deposit-induced corrosion of boiler materials in biomass combustion and recovery boilers - Eriksson, Jan-Erik; Mori, Stefano; Silvander, Linus; Hupa, Leena; Lehmusto, Juho (Springer, 2025)
Various instrumental methods for analyzing high-temperature corrosion of boiler materials were explored and compared. These methods were applied to gain deeper insights into corrosion due to two salt mixtures containing Na, K, SO4, and Cl below and above the mixtures’ first melting points. Stainless steel AISI316 and high-alloyed Sanicro28, typically used in heat exchangers in power plants, were exposed to salt mixtures in a laboratory tube furnace for 168 h. The extent of the metal corrosion following exposure was measured through mass loss, changes in the surface topography using optical 3D imaging, and dimensional metrology. Additionally, the morphology, thickness, and composition of the formed oxide scales were characterized using SEM–EDX. The information gathered from each method confirmed the impact of the synthetic salt deposit and temperature on the metal corrosion. Combining several methods enables detailed studies of changes taking place on the metal surface after exposure to challenging environments. The results also suggested that partial melting of the deposit had a higher impact on the corrosion than its chloride content.
Keywords: High-temperature corrosion; Corrosion analysis; First melt temperature; 40 Engineering; 4017 Mechanical Engineering